Archéologie d’un jardin de sculptures du xxe siècle - Aline Gheysens (Projets de Paysage)
Let’s take a moment in order for us to imagine a large bramble bush which, as time goes by, has become a garden secretly gathering the sculptures collection of a great art dealer of the 20th century. It is on this unusual garden that this research will be borne, which will take the appearance of an archaeology whose modalities will be precisely determined – alternately borrowing from the methods of the anthropological investigation, from Art history or literary analysis, from the concepts of philosophy or psychoanalysis, from the practise of photography and the theories of all fields. If it matters so much to create such a modus operandi, between arts and sciences, it is because this garden asks questions to which we can answer only through these multiple approaches : first of all we shall understand the underlying logic of the organisation of this space – which does not results from a preliminary plan but was built little by little, organically. Then, we shall see what sorts of relationships may have occurred, for the creator of this garden – who was also an author – between the takeover of this place and a daily practise of writing, on the basis that what is expressed in a novel, no space could show it, while what tends to be stated by a garden would fail in any literary attempt. In other words, the garden would have to be read, and its reading should be invented. In that way, a central question in this study will concern the close connection which seems to link in this place the so-called natural element and the sculpture in their peculiar propensity to reveal a multitude of times in representation. Our investigation will aim at understanding, by multiplying the means of interpretation, what this garden can tell us about the Art history of a certain time, about linguistic connections maintained by individuals at the core of the space it offers in relation with time and even of a certain religiousness which, all by itself or through this man’s work, has found a place in this garden and which makes of this meeting between a landscape and sculptures a aesthetic experience of an unsuspected power. This work will be divided into three stages : collecting (archives, oral evidences, letters, novels...), data production (texts, photographs), careful study of these information according to an experimental protocol and finally, connecting all the produced data together in a book combining text and photography.